Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Roundtable terhadap Hasil Belajar Matematika - Eka Anjarwati; Suparni Suparni; Rahma Hayati Siregar (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
This research is motivated by the lowlearning outcomes of students, because the learning process at school still uses conventional learning models. Mathematics learning tends to be teacher-centered, resulting in students being less active in the learning process. Therefore, the researchers conducted research on the Round Table type of cooperative learning model that can affect students mathmatics learning outcomes.The formulation of the problem in this study is whether there is a significant influence of the Round Table type of coopetive learning model on students mathematics learning outcomes in the trigonometry material of Tenth Graders of SMA Negeri 2 Padang Bolak. The purpose of this study was to determine the significant influence of the Round Table type of coopetive learning model on students mathematics learning outcomes in the trigonometry material of Tenth Graders of SMA Negeri 2 Padang Bolak.This research is a quantitative study using experimental methods with the research design is non random contol group pre test post test design. The population in this study were Tenth Grade of SMA Negeri 2 Padang Bolak which consisted of three classes with a total of 79 students. The sampel in the experimental class that was given treatment amounted to 27 students and the control class that was not given treatment amounted to 25 students. Data processing and data analysis was carried out using the T-test.The result of the T-test obtainedthe average value of the experimental clas after the Round Table type of coopetive learning model was applied to the results of the pre test to the post test, which was 68,89 to 75,741. While in the control class the results of the pre test to the post test, which was 65 to 71,8. Based on the results of hypothesis testing obtained thitung ttabel (2,1758 2,008) with a significance level 5% and dk = 50, then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant influence of the Round Table type of coopetive learning model on students mathematics learning outcomes in the trigonometry material of Tenth Graders of SMA Negeri 2 Padang Bolak.